Preparation of Recipient Areas When Skin Grafting for Camouflage of Static Localised Vitiligo - S Vadodaria; T Kangesu (Indian Journal of Plastic Surgery)
A prospective randomized study was undertaken in 50 patients with static localised vitiligo to determine the optimum thickness of the excision of patches of vitiligo prior to grafting with normally pigmented very thin split-thickness skin grafts.